Correction of Thrombocytopenia with Thrombopoietin Receptor Agonists in Patients with Liver Cirrhosis Before Elective Surgery or Invasive Procedures - T. A. Deeva; M. V. Maevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
Aim: to review the pathogenesis of thrombocytopenia and possible ways of its correction in patients with liver cirrhosis before elective surgical interventions or invasive procedures to optimize clinical practice.Key points. Thrombocytopenia is a common hematological complication of liver cirrhosis, affecting up to 75–86 % of patients with decompensated cirrhosis. Thrombocytopenia is associated with increased risks of bleeding and mortality. It complicates the management of patients, especially those who require invasive procedures, many of which carry a risk of bleeding. This risk of bleeding varies with the severity of thrombocytopenia, coagulation status, and type of invasive procedure.Moderate-to-severe thrombocytopenia can interfere with life-saving interventions, such as invasive procedures/surgeries. Delayed care is associated with longer hospital stays and greater medical costs. Thrombopoietin receptor agonists (avatrombopag) should be considered for the management of cirrhotic patients with severe thrombocytopenia undergoing elective invasive interventions with a high risk of bleeding.Conclusion. Thrombopoietin receptor agonists (avatrombopag) have demonstrated high efficacy and safety and are considered a promising first-line option for the management of severe thrombocytopenia in patients with liver cirrhosis undergoing elective surgical interventions or invasive procedures.